The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Organic Reactions 1999
DOI: 10.1002/0471264180.or055.01
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Of Nucleosides

Abstract: This chapter deals with the synthesis of nucleosides (e.g., the formation of N ‐glycosides of sugars such as D ‐ribose or 2‐deoxy‐D‐ribose with heterocyclic nitrogen bases). The methods of nucleoside synthesis have been treated in a number of reviews and monographs. It is now generally accepted that nucleosides were among the first organic compounds formed at the start of evolution in the early history of our planet earth. To sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
201
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(213 citation statements)
references
References 1,288 publications
1
201
0
4
Order By: Relevance
“…Thus, the pyrazoline cycloadducts are initially formed, but these are unstable and spontaneous elimination of R 1 S(O)Cl gives the pyrazoline intermediate, which on 1,5-trimethylsilyl shift affords the N-trimethylsilyl pyrazole. Hydrolytic cleavage of the N-Si bond [36][37][38][39][40] (presumably when the crude product is purified by chromatography on silica gel) yields the final pyrazole product (Scheme 10).…”
Section: -Fluorophenyl-and N-benzyl-benzylthio Derivatives 19 and 28mentioning
confidence: 99%
“…Thus, the pyrazoline cycloadducts are initially formed, but these are unstable and spontaneous elimination of R 1 S(O)Cl gives the pyrazoline intermediate, which on 1,5-trimethylsilyl shift affords the N-trimethylsilyl pyrazole. Hydrolytic cleavage of the N-Si bond [36][37][38][39][40] (presumably when the crude product is purified by chromatography on silica gel) yields the final pyrazole product (Scheme 10).…”
Section: -Fluorophenyl-and N-benzyl-benzylthio Derivatives 19 and 28mentioning
confidence: 99%
“…Two approaches to the synthesis of purine nucleosides have been widely and extensively studied. The first, convergent approach consists in the condensation of a purine base with a suitable pentofuranose derivative and subsequent deprotection (see, e.g., [5,6,9] and the reviews [10] ). The second comprises the chemical transformation of the purine base or/and the pentofuranose fragment of the natural commercially available ribo-or 2'-deoxyribo-nucleoside in the desired compound.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the b-oriented glycoside bond their use appears to be a convenient alternative to chemical methods which suffer from low stereoselectivity, multi-step procedures and modest total yields. [3] Several procedures based on the "transglycosylation" reaction (Scheme 1) have been employed (using both isolated enzymes and whole cells) to prepare a wide variety of nucleosides. [4][5][6][7][8][9][10][11] Structural analysis revealed that there are two distinct families of NPs: NPI and NPII.…”
Section: Introductionmentioning
confidence: 99%